The mass-count distinction in Dutch-speaking children with specific language impairment - Jeannette Schaeffer; Merel Van Witteloostuijn (Glossa, 2018)
This study reports experimental data on the acquisition of the mass-count distinction by Dutch-speaking children with specific language impairment (SLI). While verbal morphosyntax is known to be impaired in SLI, nominal morphosyntax has received less attention. The mass-count distinction provides an interesting test ground: count can have a plural morpheme: bal-en (‘balls’), but mass cannot: *deeg-en (‘doughs’). Flexible nouns can easily occur in either mass or count syntax (pizza/pizza-s). Finally, object-mass nouns (e.g. furniture) are syntactically mass, but quantify over individuals, and are hypothesized to have a lexical [+individual] feature (Bale & Barner 2004). Typically developing (TD) Dutch-acquiring children become sensitive to the mass-count distinction around age 6 (van Witteloostuijn 2013).Hypothesizing that the primary impairment of SLI is in morphosyntax, and not in lexical-semantics, we predict that Dutch-speaking children with SLI older than 6 have most problems with the interpretation of flexible nouns (relying solely on morphosyntax), some problems interpreting classical count and mass nouns (supported by convention/world knowledge), and least problems interpreting object–mass nouns (relying solely on their lexical [+individual] feature). Quantity judgments based on count and mass nouns were collected from 28 Dutch children with SLI aged between 6 and 14 years old and 28 individually age-matched TD children. Confirming our predictions, the children with SLI scored significantly lower than their TD controls on flexible nouns, and, albeit to a lesser extent, on classical nouns. This underscores the (nominal) morphological deficit in SLI. In contrast, no difference between groups was found on object-mass nouns.